Habutobin Splits the Arg16-Gly17 Bond in the Aa Chain of Rabbit Fibrinogen - Kinjoh, Kiyohiko; Kosugi, Tadayoshi; Nakamura, Mariko; Hanashiro, Kazuhiko; Sunagawa, Masanori; Tokeshi, Yoshihiro; Eguchi, Yukinori (Thrombosis and Haemostasis, 1997)
We reported previously that habutobin, a thrombin-like enzyme from Trimeresurus flavoviridis venom, clotted only rabbit fibrinogen, whereas human, monkey, bovine, dog, rat and guinea-pig fibrinogens were unaffected. In the present study, we investigated the cleavage site of the rabbit Aα chain by habutobin. The fibrinopeptide released by habutobin was identical to the fibrinopeptide A released by thrombin, and its amino acid sequence corresponded to Aα 1-16 of rabbit fibrinogen. It was clarified therefore that habutobin cleaves the Arg16-Gly17 bond in the Aa chain of rabbit fibrinogen.